Pengaruh lingkungan kerja dan stres kerja terhadap kinerja pegawai di dinas perhubungan Provinsi Sumatera Selatan - Yunike Yunike; Hamid Halin; Yeni Yeni (Nur Science Institute, 2026)
This study aims to examine the effects of the work environment and job stress on employee performance at the Transportation Agency of South Sumatra Province. A quantitative approach with a survey design was employed, involving 99 respondents selected through purposive sampling. Data were analyzed using multiple linear regression after passing validity and reliability tests to ensure data quality. The results indicate that both the work environment and job stress have positive and significant effects on employee performance, both partially and simultaneously. A supportive work environment enhances employee comfort and productivity, while job stress at an optimal level can stimulate motivation in task completion. These findings highlight the importance of organizational efforts to create a conducive work environment and to effectively manage job stress to sustainably improve employee performance. In addition, this study offers practical implications for public sector institutions seeking to enhance human resource effectiveness.